Assessing the market power of millers and wholesalers in the Bangladesh rice sector. Issue 3 (21st July 2020) - Rahman, Mohammad Chhiddikur; Pede, Valerien; Balie, Jean; Pabuayon, Isabelita M.; Yorobe, Jose M.; Mohanty, Samarendu
Abstract : Purpose: Because of the increasing differential between farm and retail prices, the study proposes to investigate the extent of market power in the rice value chain of Bangladesh using advanced econometric techniques. Design/methodology/approach: Using a Stochastic Frontier Estimation approach on cross-sectional data, the study examines the price spread along the rice value chain to determine whether millers and wholesalers exercise market power. Findings: Empirical results reveal that, on average, rice millers and wholesalers charge 33 and 29% above the marginal cost, respectively. This study confirms the non-competitive behavior of the rice market with wholesalers and millers wielding substantial market power Research limitations/implications: A limitation of the study is that it does not include the retailers who also play a major role in the Bangladesh rice value chain. This is left for future study. Originality/value: This study combines primary and secondary data collected on the Bangladesh rice sector to examine the market power of two major players along the value chain, millers and wholesalers, using an advanced econometrics approach.